2018
DOI: 10.1038/s41598-018-32238-z
|View full text |Cite
|
Sign up to set email alerts
|

The sense of agency shapes body schema and peripersonal space

Abstract: Body schema, a sensorimotor representation of the body used for planning and executing movements, is plastic because it extends by using a tool to reach far objects. Modifications of peripersonal space, i.e., a functional representation of reach space, usually co-occur with body schema changes. Here, we hypothesized that such plastic changes depend on the experience of controlling the course of events in space trough one’s own actions, i.e., the sense of agency. In two experiments, body schema and peripersonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 51 publications
0
51
0
Order By: Relevance
“…Overall, these results suggest that actions can drive a potential modification of body metric representation per se, possibly because of the agency experienced during the training (D'Angelo, et al, 2018), that integrates with the morphological and functional features of the tool.…”
Section: Experiments 2 Short Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Overall, these results suggest that actions can drive a potential modification of body metric representation per se, possibly because of the agency experienced during the training (D'Angelo, et al, 2018), that integrates with the morphological and functional features of the tool.…”
Section: Experiments 2 Short Discussionmentioning
confidence: 82%
“…This effect is potentially related to the sense of agency modulated during the training. Indeed, it was recently shown that agency is involved in body schema and peripersonal space modulation (D'Angelo, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…And this was enough for the perceived arm length increase to occur, or so the authors argued. In a similar vein, a very recent study on healthy subjects has demonstrated that body metric estimation can be modulated by the sense of agency (D’Angelo et al, 2018). Participants were asked to perform a forearm bisection task before and after a training phase, in which they virtually grasped objects and make precision grip by controlling a far 3D virtual hand.…”
Section: Discussionmentioning
confidence: 93%
“…In the context of virtual reality, another study demonstrated that body metric estimation can be modulated by motor embodiment (D'Angelo et al, 2018). Participants were asked to perform a forearm bisection task before and after a training phase, in which they virtually grasped objects on a PC screen with a virtual hand.…”
Section: Tools and Virtual Realitymentioning
confidence: 99%